Analisis Tren Perkembangan E-Commerce di Asia Tenggara Menggunakan Data Google Trends - Gulo, Famoboro; Halawa, Serius; Telambanua, Aldin Noverman (CV. SINAR HOWUHOWU, 2025)
This research analyzes e-commerce development trends in Southeast Asia using Google Trends data from 2015 to 2023, incorporating digital payment systems evolution, generational shopping behaviors, and COVID-19 impacts. Results indicate substantial growth variations across countries, with notable differences in digital payment adoption and consumer preferences. The study reveals that e-commerce growth is driven by mobile commerce adoption, social media integration, and digital payment infrastructure development (Wong & Huang, 2019). Our findings provide strategic insights for e-commerce stakeholders and policymakers in navigating the region's dynamic digital marketplace.